Annotated bibliography addressing the international pedigrees and flows of plant genetic resources for food and agriculture: Information document submitted by the System-wide Genetic Resources Programme of the CGIAR to the Eighth Conference of the Parties to the Convention on Biological Diversity (COP 8) and the Ad Hoc Open-ended Working Group on Access and Benefit-sharing - Frison, C.; Halewood, Michael; CGIAR Systemwide Genetic Resources Programme (2006)
This bibliography was developed by Christine Frison, consultant, and Michael Halewood of the International Plant Genetic Resources Institute (IPGRI). IPGRI thanks the following individuals for their contributions: Cary Fowler, Jane Toll, Jan Engels, Toby Hodgkin, Samy Gaiji, Coosje Hoogendoorn, Robert Lewis-Lettington, Olivier Hanotte, Adam Drucker, Workneh Ayalew, Jean Hanson, Ruaraidh Sackville Hamilton, Mike Jackson, Graham McLaren, Melinda Smale, Reem Hajjar, Hari D. Upadhyaya, C.L.L. Gowda, Douglas Gollin, Thomas Carter, Ricardo Cardellino, Kent Nnadozie, Clive Stannard, Irene Hoffman, Sirkka Immonen, Jonathan Robinson, Roland von Bothmer, Kameswara Rao, Shawn Sullivan, Masa Iwanaga and Ilse Kohler-Rollefson. For more information about this bibliography and or suggestions for additional entries, contact Michael Halewood, Policy Research and Support Unit, IPGRI, at mailto:M.Halewood@cgiar.org